The Influence of Population and GRDP on Community Consumption in North Sumatra Province - Handayani, Siti Alifah; Tampubolon, Agustin Mahardika; Kurnia, Tri; Siagian, Arnol Prabowo; Rambe, Rolil (Economic: Journal Economic and Business, 2024)
This research aims to analyze the influence of population and GRDP on people's consumption levels in North Sumatra Province. This research uses a regression model using the Error Correction Model (ECM) method and uses secondary data. The research results show that Population and GRDP have a positive and significant impact on public consumption in the long term, but there is no significant impact in the short term. The regression model shows a positive relationship between the variables Population, GRDP, and Public Consumption. The classical assumptions of this model are met. This research provides important insights regarding economic development policies, sustainable population growth, and balanced GRDP growth. Factors such as income, unemployment and economic conditions also influence people's consumption patterns. Suggestions for further research are also suggested to gain a deeper understanding of the factors that influence public consumption in the region.